Effect of Low Partial Vacuum on Evaporation and Condensation Performance in a Solar Still System - Irfan Maulana Yusuf; Dan Mugisidi; Oktarina Heriyani; Sofia Pinardi; Nunik Pratiwi (Jurnal ASIIMETRIK Jurnal Ilmiah Rekayasa & Inovasi, 2026)
This study investigates the effect of low partial vacuum on the evaporation and condensation performance in a solar still system. The tests were conducted using three variations: non-vacuum (101325 Pa), vacuum 1 (101313 Pa), and vacuum 2 (101309 Pa) using an exhaust system. The observed parameters included water temperature, pressure, vapor pressure difference (ΔP), evaporation mass, and condensation yield. The results showed that low partial vacuum increased the vapor pressure difference, thereby enhancing the driving force for evaporation. The highest maximum ΔP value was obtained at vacuum 2, at 1278.48 Pa. However, water temperature had a more dominant influence on total evaporation, so the highest cumulative evaporation mass was obtained under non-vacuum conditions at 8750 g due to better thermal energy retention. Meanwhile, vacuum 1 produced the highest condensation yield of 7641 g, indicating a balance between vapor formation and vapor distribution within the system. These findings suggest that the optimization of a solar still based on low partial vacuum is determined not only by an increase in vapor pressure difference but also by the system’s ability to retain thermal energy and the effectiveness of the condensation process .